2007
DOI: 10.1152/ajpheart.00925.2006
|View full text |Cite
|
Sign up to set email alerts
|

O2delivery and redox state are determinants of compartment-specific reactive O2species in myocardial reperfusion

Abstract: Stoner JD, Clanton TL, Aune SE, Angelos MG. O2 delivery and redox state are determinants of compartment-specific reactive O2 species in myocardial reperfusion. Am J Physiol Heart Circ Physiol 292: H109 -H116, 2007. First published October 6, 2006; doi:10.1152/ajpheart.00925.2006.-Reperfusion of the ischemic myocardium leads to a burst of reactive O2 species (ROS), which is a primary determinant of postischemic myocardial dysfunction. We tested the hypothesis that early O2 delivery and the cellular redox state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…It is interesting that low levels of NADH production were maintained even though heart rate returned to the pre-ischemic level: 196 ± 12 bpm before ischemia and 183 ± 12 bpm after ischemia (p = 0.096). It is unlikely that the imposed 20 min of global ischemia confounded (other than the injury itself) the NADH ED-FRAP signal observed after 10 min of reperfusion given the rapid oxidation of NADH and restoration of fNADH to a level similar to that before ischemia, analogous to previous studies of ischemia in isolated hearts464748.…”
Section: Discussionsupporting
confidence: 53%
“…It is interesting that low levels of NADH production were maintained even though heart rate returned to the pre-ischemic level: 196 ± 12 bpm before ischemia and 183 ± 12 bpm after ischemia (p = 0.096). It is unlikely that the imposed 20 min of global ischemia confounded (other than the injury itself) the NADH ED-FRAP signal observed after 10 min of reperfusion given the rapid oxidation of NADH and restoration of fNADH to a level similar to that before ischemia, analogous to previous studies of ischemia in isolated hearts464748.…”
Section: Discussionsupporting
confidence: 53%
“…ROS production in perfused hearts was measured using the fluorescent probes dihydroethidium (DHE) and dihydrofluorescein (DHF) diacetate (DHFDA) as previously described (22,42). DHFDA passes through cell membranes and is converted to DHF by intracellular esterase and then oxidized to green fluorescein.…”
Section: Animalsmentioning
confidence: 99%
“…Following cardiopulmonary bypass pulsatile flow is restored, and ischemic tissues may be reperfused. In experimental models markers of oxidative damage surge following reperfusion [79, 28]. Markers of oxidative stress also surge after cardiopulmonary bypass [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that intraoperative oxidative damage, quantified by measuring plasma concentrations of F 2 - isoprostanes, independently predicts AKI following cardiac surgery [2]. Excess oxygen exposure (hyperoxia) induces excessive reactive oxygen species (ROS) production in cell-culture and ischemia reperfusion experiments [79]. Similarly, hyperoxic reperfusion of ischemic tissues is associated with tissue damage and poor outcomes in some patient populations [1012].…”
Section: Introductionmentioning
confidence: 99%